A study of data components and knowledge components for plant biodiversity area by using spatio-temporal data model techniques - Wahid, Mohd. Taib; Abdul, Abd. Mannan; Selamat, Harihodin; Zakaria, Norhidayati (Faculty of Computer Science and Information System, 2006)

(untitled)
The economic importance and uses of the large number of biodiversity plant species of Malaysia make it essential for their biodiversity to be conserved. The complexity of natural history collection information and similar information within the scope of biodiversity informatics poses significant challenges for effective management of plant biodiversity data. In order to undertake the steps for biodiversity conservation such as identification of species, monitoring climate conditions, it is essential to efficiently manage the vast amount of biodiversity related data. This project discussed about the object-relational conceptual design of biodiversity data model for long term stewardship of biodiversity information. In this research design a biodiversity data model that better facilitates the exploration and analysis of spatio-temporal biodiversity data by using object relational data model techniques. The conceptual model that is efficient for data management and able to integrate diverse set of spatio-temporal data for analysis, and monitoring biodiversity data. Moreover, forest department, land and agricultural management and other related research organization could be benefited from this research.